2021
DOI: 10.1039/d1ma00247c
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the physiochemical aspects of the matrix in improving sulfur-loading for room-temperature sodium–sulfur batteries

Abstract: The physiochemical aspects of the matrix play an important role in deciding the loading of sulfur cathodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 194 publications
(246 reference statements)
0
13
0
Order By: Relevance
“…Design for reusability is an upgraded step to record design data, recover previous data and use previous design knowledge for reusability of already used parts and products. By focusing on design for reusability guidelines, environmental impact can be significantly reduced because of reduction in material waste and landfill waste, and it also reduces material and energy consumption by using existing components (Bras and McIntosh, 1999; Sungjemmenla et al , 2021). Guideline “Optimize part orientation for build time and roughness” needs to give more priority.…”
Section: Resultsmentioning
confidence: 99%
“…Design for reusability is an upgraded step to record design data, recover previous data and use previous design knowledge for reusability of already used parts and products. By focusing on design for reusability guidelines, environmental impact can be significantly reduced because of reduction in material waste and landfill waste, and it also reduces material and energy consumption by using existing components (Bras and McIntosh, 1999; Sungjemmenla et al , 2021). Guideline “Optimize part orientation for build time and roughness” needs to give more priority.…”
Section: Resultsmentioning
confidence: 99%
“…53,54,67 Due to their high electronegativity and small atomic diameter, nitrogen atoms are able to improve battery performance by binding to sulfur species and facilitating sulfur immobilization. 59,68,69 For the ZIF-8derived MPC cathodes reported by Eng et al, higher nitrogen doping was found to lead to superior long-term cycling stability and Coulombic efficiency despite having lower electrical conductivity and reaction kinetics. 54 Moreover, it was observed that varying the carbonization temperatures of the MOF precursors (800-1000°C) effectively tuned the nitrogen doping, with lower carbonization temperatures resulting in higher nitrogen contents.…”
Section: Doping Of Host Structuresmentioning
confidence: 94%
“…[ 68,85 ] Besides the formidable challenges, the system experiences overall degradation in performance and low utilization of sulfur cathode. [ 86 ] Therefore, extensive research has been put forward with a rational combination of matrices for the S‐host to surmount the drawbacks mentioned above. Recently, significant progress in engineering the cathode structure has been made.…”
Section: Progress Toward Cathode System In a Metal–sulfur Interacted ...mentioning
confidence: 99%
“…As the sulfur loadings are further enhanced, the IR drop is augmented, hindering the uptake of electrolyte ions. [ 86 ] In‐depth mechanistic studies need to be conducted to develop new chemistries to enhance the S‐loadings without compromising the reaction kinetics and cycle life of the cell.…”
Section: Outlook and Future Perspectivementioning
confidence: 99%